Investigating the significant variation of coal consumption in China in 2002-2017. (15th September 2020) - Liu, Lan-Cui; Cheng, Lei; Zhao, Lu-Tao; Cao, Ying; Wang, Ce
Abstract: From 2002 to 2017, China's coal consumption underwent a significant change, from a rapid growth to slow decline. Aimed to provide some suggestions for the further coal removal, this study focuses on this significant change and analyzes the coal consumption in supply chains using structural path analysis and structural path decomposition models. Coal consumption driven by fixed capital formation constituted almost 50% or more of coal consumption for the critical 59 paths. Except for coal intensity, production structure was another main mitigating factor of this growth from 2007. The decline in coal consumption caused by coal intensity (2002–2012) and production structure (2007–2012) could only partially offset the increased consumption caused by other factors; thus, coal consumption had the most rapid growth in 2002–2012. In 2012–2017, the decline caused by the coal intensity, production structure, and commodity structure fully offset the increase mainly due to final demand per capita; therefore, there was a historical decrease in coal consumption, breaking the continuous growth trend since 1980. Coal intensity reduction and production structure adjustment should be the key target for short-term control of coal consumption. Meanwhile, the structures should be adjusted toward items that have lower coal consumption in the long-term. Highlights: The determinants behind increased and decreased coal consumption are identified. The 40 highest-ranking paths vary greatly for different years. Coal intensity is the driver that mitigates coal consumption growth. Production structure is a main factor mitigating coal consumption growth.